A research on packaging on product: Candlenuts by Nadia / Nur Syahira Idris - Idris, Nur Syahira (2022)
Packaging is the most important and successful tool to attract customers into buying a product. A good packaging design will increase brand loyalty among the customers. Therefore, this research aims to find out the impact of packaging design on customers and to identify the elements, which should be highlighted while designing the packaging. This research will focus on Therapeutic Candle Meltz packaging from the brand Candlenuts by Nadia. Candlenuts by Nadia is a local scented candle melts brand. It is the first brand that introduces candle melts in Malaysia so it has a good potential to become a big candle brand like Bath & Body Works in the future. The problem that led to this research is the packaging. The packaging is transparent and there are many waxy residues on the packaging. Also, the labelling design is not attractive to catch customer attention. These problems make the product looks less attractive in customers' eyes. In this research, the collection of data will be using a quantitative method. A total of 118 respondents participated in the survey about the most important things should have in product packaging. The survey will tell how important packaging and labelling design is to attract and convinced a customer to buy the product. The survey also includes whether the customer will buy the product with the problematic packaging and labelling design. Finally, it has been concluded that packaging design is indeed an important factor to influences customers to buy a product. Most of the respondents agree that a good packaging and unique labelling design can make people trust the brand. The packaging elements such as colour, packaging material, design of packaging, and innovation are the important factor of customers buying decisions.